2006
DOI: 10.1007/bf02969399
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effects of young radish cultivated with sulfur on growth and metastasis of B16-F10 melanoma cells

Abstract: The oral administration of extracts of young radishes cultivated with sulfur after intravenous tumor cell injection achieved a marked reduction of pulmonary colonization in mice. Treatment of the mice with extracts of young radish cultivated with sulfur did not show any increase in the number of CD8+ or NK T cells in the spleen, indicating no influence on host immunity. Sulforaphane, which could be a candidate for an active compound from young radishes cultivated with sulfur, inhibited cell growth of B16-F10 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Some previous reports have shown that SFN could be effective in treating melanoma, but virtually all promising results have thus far been obtained from animal studies. Specifically, SFN was shown to inhibit the metastasis of B16F-10 mouse melanoma cells both in vivo and in vitro [ 21 ]. In a murine model, SFN was shown to induce a significant reduction in the expression of cell proliferation markers (metalloproteinases 2 and 9), leading to an increase in the survival rate of animals bearing metastatic tumours, probably via stimulating a cell-mediated immune response [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some previous reports have shown that SFN could be effective in treating melanoma, but virtually all promising results have thus far been obtained from animal studies. Specifically, SFN was shown to inhibit the metastasis of B16F-10 mouse melanoma cells both in vivo and in vitro [ 21 ]. In a murine model, SFN was shown to induce a significant reduction in the expression of cell proliferation markers (metalloproteinases 2 and 9), leading to an increase in the survival rate of animals bearing metastatic tumours, probably via stimulating a cell-mediated immune response [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the antioxidant ( ) and antimutagenic properties () of radishes and the phytochemicals derived from radishes, and recently there have also been published reports of radishes increasing detoxification enzyme activity ( , ). The high glucosinolate concentration found in SBR suggests the possibility that it may be a potent inducer of detoxification enzymes when individuals are exposed to the food through the diet.…”
Section: Introductionmentioning
confidence: 99%
“…However, radishes are a far more popular vegetable in other countries, and in fact the daikon, a large white radish that also contains glucoraphasatin as a vast majority of the glucosinolates present, is one of the most commonly consumed vegetables in Japan (14,15). Previous studies have demonstrated the antioxidant (16)(17)(18)(19)) and antimutagenic properties (20) of radishes and the phytochemicals derived from radishes, and recently there have also been published reports of radishes increasing detoxification enzyme activity (21,22). The high glucosinolate concentration found in SBR suggests the possibility that it may be a potent inducer of detoxification enzymes when individuals are exposed to the food through the diet.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro experiments have demonstrated that radish roots have potent antioxidant activity (Barillari et al, 2006), induce detoxification enzymes Hanlon et al, 2007) and inhibit proliferation of cancer cells (Kim et al, 2006;Barillari et al, 2008;Papi et al, 2008). In vivo experiments focusing on the activity of the radish root have also shown that radish consumption protects against chemical-induced injury (Baek et al, 2008) and reduces oxidant stress (Sipos et al, 2002;Lugasi et al, 2005).…”
Section: Introductionmentioning
confidence: 96%